Use of Picture Card Games to Improve Children's English Language Skills in Kindergarten - St. Maria Ulfah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study aims to determine the use of picture cards in making learning media for early childhood. Card games often involve an element of repetition, be it in the form of game rules or in the practice of matching cards. This repetition helps to strengthen the child's memory of the vocabulary learnt. Meanwhile, the lecture method tends to be boring in introducing children to vocabulary in English. Picture cards provide a visual stimulus that helps children associate pictures with specific English words, making it easier to recognise and understand new vocabulary. The method used is a qualitative research approach. The subjects to be studied are teachers who have used English picture cards totaling 5 teachers at Aisyiyah Lutang Majene Kindergarten. Data collection techniques in this study were observation, documentation, and interviews using previously validated instruments. The results showed that by using picture card media. The ideas that teachers find when using picture card media, are adjusted to the teacher's ability to support English language learning activities in the classroom